The gender differences in the implementation and maintenance of a structured-enhanced education and follow-up program in primary prevention for coronary artery disease. (14th October 2021) - Soran, O; Karadeniz, P G; Uygunlar, M; Hengirmen, B; Durak, T; Tibet, B N; Inan, M F; Cepik, E H; Unal, E; Saglam, B A; ,
Abstract: Background: Primary prevention programs for coronary artery disease (CAD) may be effective in improving health-related behavioral outcomes. However, successful implementation and maintenance of these programs can vary amongst genders. The primary aim of this study is to assess the gender differences in a structured, enhanced education and follow-up program for CAD prevention in an area where the diverse population and economy are major problems. Methods: SANKO CAD Prevention Project (SCAD-PPI) was designed as a longitudinal study and utilized medical school students to conduct the project under the supervision of professors. It began in 2014 and had two different education and training phases. In the first phase, every school year for second year Medical students underwent a year-long, especially designed training program on primary prevention for CAD. In the second phase, which took place in the second year of the study, a series of conferences regarding the primary prevention for CAD were organized by the University and local municipalities for underserved populations. Participants were prospectively assigned to an intervention where pre- and post-conference knowledge was collected and assessed. Every intervention was conducted by specially trained third year Medical students and an education booklet, which was specially designed for the study, was given to the participants. Every other month thereafter, for 6 months, each participant was followed-up via phone calls. At the 6 months follow -up, data was collected to assess the impact of the program on behavioral outcomes. Every year a new class assigned to undergo the same training program and serve to the local population at different locations within the same city and suburbs. Results: A total of 172 participant were enrolled; 61% were women, mean age was 40±11.9 years with no significant difference in between the groups.; 67% of women were not working (p<0.001). While BMI rates were higher in women (27.9±5.5 kg/m 2, p<0.016), smoking rates were higher in men (p<0.001). Overall, knowledge on CAD risk factors, primary prevention measures, diet, and daily exercise habits were poor in both groups. After the enhanced education and follow-up program there was a significant improvement on the knowledge of CAD risk factors and primary prevention measures in both groups (p<0.001). Importantly, the follow-up program led both groups to implement those positive changes into their lives and maintain a healthy lifestyle. Conclusion: This is the first study which showed that a longitudinally structured training program of medical students could be utilized to implement an enhanced education and follow–up program for primary prevention of CAD in an economically challenged, underserved population with successful outcomes in both genders. This model program is not only beneficial for public interest, but also enhances active interaction of medical students with patients at a very early stage of their career. FUNDunding Acknowledgement: Type of funding sources: None.